Neuropeptide Y prolongs non-social memory in a brain region- and receptor-specific way in male mice - Kornhuber, Johannes; Zoicas, Iulia (Neuropharmacology, 2020)
Neuropeptide Y (NPY) and its receptors are highly expressed in brain regions involved in learning and memory processes. We have previously shown that intracerebroventricular administration of NPY prolongs the retention of non-social memory in the object discrimination test. Here, we aimed to identify the brain regions which mediate these memory-enhancing effects of NPY. We show that NPY (0.1 nmol/0.2 μl/side) prolongs retention of non-social memory when administered into the dorsolateral septum (DLS) and medial amygdala (MeA), but not when administered into the dorsal hippocampus, central amygdala and basolateral amygdala. In the DLS, the effects of NPY were blocked by the Y1 receptor antagonist BIBO3304 trifluoroacetate (0.2 nmol/0.2 μl/side), but not by the Y2 receptor antagonist BIIE0246 (0.2 nmol/0.2 μl/side). In the MeA, on the other hand, BIIE0246, but not BIBO3304 trifluoroacetate blocked the effects of NPY. This study demonstrates that NPY exerts Y1 receptor-mediated memory-enhancing effects in the DLS and Y2 receptor-mediated memory-enhancing effects in the MeA, and suggests that distinct brain regions and receptor subtypes are recruited to mediate the effects of NPY on non-social memory.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Discrimination memory; Local infusion; Memory retention; Object investigation; Object memory